CORPORATE LEADERSHIP EXPOSED DURING COVID 19 - Anand, Tirupathi; Banerjee, Arindam; Riaz, Sadia (International Journal of Research -GRANTHAALAYAH, 2020)
The sudden onset of the pandemic called COVID 19 took the entire world by shock and surprise. The reaction time was very less as most of the countries went into a lockdown to contain the spread of the virus. People were least prepared for the pandemic and its waterfall effects. The businesses were mostly reactive and internally started creating panic among employees and other stakeholders. This article is an attempt to explore the after effects of COVID 19 and how the Corporate Leadership got completely exposed during the pandemic.